2007
DOI: 10.1038/sj.clpt.6100023
|View full text |Cite
|
Sign up to set email alerts
|

Selective AT1 Receptor Antagonism Enhances Sympathetically Mediated Vasoconstriction in Man

Abstract: The vasoconstrictive action of angiotensin II (AII) is partly, sympathetically mediated and angiotensin-converting enzyme (ACE) inhibitors appear to exert a sympatholytic effect. We examine the effect of an orally administered, selective AT(1) receptor antagonist (losartan 50 mg) on sympathetically mediated vasoconstriction in healthy volunteers in an observer blind crossover study. Seven healthy, normotensive volunteers (21-32 years), were studied on two occasions at the end of each 6-week treatment period (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…It has been demonstrated that the RAS can interact with the sympathetic nervous system in a stimulatory manner at several different levels of the neuronal network [13]. AngII is well known to facilitate the release of noradrenaline from sympathetic nerve terminals in many tissues including the heart, kidney and blood vessels [30][31][32]. In contrast, a previous study did not confirm the role of AngII in the increased noradrenaline release or reduced noradrenaline reuptake in a hypertensive population [33].…”
Section: Discussionmentioning
confidence: 94%
“…It has been demonstrated that the RAS can interact with the sympathetic nervous system in a stimulatory manner at several different levels of the neuronal network [13]. AngII is well known to facilitate the release of noradrenaline from sympathetic nerve terminals in many tissues including the heart, kidney and blood vessels [30][31][32]. In contrast, a previous study did not confirm the role of AngII in the increased noradrenaline release or reduced noradrenaline reuptake in a hypertensive population [33].…”
Section: Discussionmentioning
confidence: 94%